Salt-fog corrosion resistant stainless steel and method for manufacturing the same
Patent Information
- Application Number
- CN202611129827.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
AI Technical Summary
(1)梯度氮分布技术仅涉及氮的单一梯度构建,强度提升主要依赖氮的固溶强化,进一步提升空间有限
本发明通过气氛固溶处理构建从表层到心部连续递减的氮浓度梯度,使表层高氮层增强钝化膜稳定性,同时为后续离子渗氮过程中VN纳米析出相的原位形成提供充足的氮源;通过V微合金化与低温离子渗氮的协同配合,在表层形成大量弥散分布的VN和/或V(C,N)纳米析出相,利用VN与奥氏体基体的共格强化效应大幅提升材料强度;通过在含V氮化物析出相层表面构建激光微孔阵列,使石墨烯复合涂层渗入微孔形成机械互锁结构,显著提高涂层与基体的界面结合强度;通过超低碳、高氮、Mo和Cu的复合耐蚀设计,从抑制Cr23C6析出、增强钝化膜稳定性、抵抗Cl-点蚀和形成表面吸附防护层等多重机制协同提升耐蚀性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of steel material processing technology, and more specifically to a salt spray corrosion resistant stainless steel and its preparation method. Background Technology
[0002] Austenitic stainless steel is widely used in marine engineering, shipbuilding, and coastal building structures due to its excellent comprehensive properties. However, in high-salt-spray environments such as the ocean, traditional austenitic stainless steels (such as 304 and 316L) are prone to pitting corrosion and intergranular corrosion, which seriously restricts their long-term service safety.
[0003] To improve the corrosion resistance of austenitic stainless steel, existing technologies include methods for creating a nitrogen concentration gradient distribution on the material surface through atmospheric solution nitriding. For example, Chinese invention patent CN118996323A discloses a gradient nitrogen-containing austenitic stainless steel, its preparation method, and its application. This method utilizes a process route of "one-time solution nitriding + large plastic cold deformation + secondary short-time solution nitriding" to obtain a gradient nitrogen-containing austenitic stainless steel with finer and controllable grain size. Furthermore, Chinese invention patent 202311782930.2 discloses a composite diffusion layer on the stainless steel surface, its preparation method, and its application. This method combines gradient ion nitriding with chromium diffusion to obtain a gradient diffusion layer structure consisting of a CrN+Cr2N layer and a nitrided austenitic diffusion layer.
[0004] However, the aforementioned existing technologies still have the following shortcomings: (1) Gradient nitrogen distribution technology involves only the construction of a single nitrogen gradient, and the strength improvement mainly depends on the solid solution strengthening of nitrogen, with limited room for further improvement.
[0005] (2) The gradient ion nitriding composite diffusion layer technology uses chromium diffusion treatment to construct a CrN+Cr2N layer. Although it improves the surface hardness and wear resistance, the precipitation of CrN will consume the chromium in the matrix, which may have an adverse effect on the corrosion resistance of stainless steel. Summary of the Invention
[0006] The purpose of this invention is to provide a salt spray corrosion resistant stainless steel and its preparation method to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides a salt spray corrosion resistant stainless steel, wherein the stainless steel comprises a stainless steel substrate and a composite protective layer laminated on the surface of the stainless steel substrate. The stainless steel matrix comprises, by mass percentage: C 0.02-0.05%, Si 0.3-0.8%, Mn 3.0-6.0%, Cr 20.0-22.0%, Ni 5.0-8.0%, Mo 1.6-3.0%, Cu 0.8-2.0%, N 0.20-0.40%, V 0.02-0.15%, RE 0.01-0.10%, P≤0.030%, S≤0.0020%, with the balance being Fe and unavoidable impurities; The RE is at least one of the rare earth elements Ce, La and Y; The nitrogen (N) content in the stainless steel matrix exhibits a gradient distribution along the thickness direction, with the surface layer containing 0.35-0.60% Ns and the core containing 0.15-0.25% Nc, and the Ns-Nc ratio ≥ 0.10%. The composite protective layer consists of, from the inside out: a nitrogen diffusion layer, a V-containing nitride precipitate layer, and a graphene composite coating. The V-containing nitride precipitate layer is formed in situ on the surface of the stainless steel substrate.
[0008] C (carbon): 0.02-0.05%. Carbon is an austenite-forming element and an interstitial solid solution strengthening element. This invention controls the C content within an ultra-low carbon range of 0.02-0.05%, fundamentally suppressing Cr... 23 The precipitation of C6 at grain boundaries eliminates the source of intergranular corrosion. The ultra-low carbon design also ensures that corrosion resistance is not compromised by carbide precipitation during subsequent atmospheric solution treatment and ion nitriding.
[0009] Si (silicon): 0.3-0.8%. Silicon is a deoxidizing element; an appropriate amount of silicon can improve the cleanliness of molten steel. This invention controls the Si content at 0.3-0.8%, ensuring the deoxidation effect without compromising the material's toughness and processing performance.
[0010] Mn (Manganese): 3.0-6.0%. Manganese is an austenite-forming element that can partially replace expensive Ni, reducing alloy costs. Simultaneously, Mn can increase the solubility of N in molten steel. This invention controls Mn within a suitable range of 3.0-6.0%, fully utilizing its role in stabilizing austenite and improving nitrogen solubility, while strictly controlling the S content (≤0.0020%) to suppress the harmful effects of MnS inclusions.
[0011] Cr (chromium): 20.0-22.0%. Chromium is the core element for stainless steel to achieve corrosion resistance, and it can form a dense Cr2O3 passivation film on the material surface. This invention controls the Cr content at 20.0-22.0%, and combines it with the synergistic effect of austenite-forming elements such as Ni, Mn, and N to ensure a stable austenitic structure, while the passivation film has excellent density and stability.
[0012] Ni (Ni): 5.0-8.0%. Nickel is an important austenite stabilizing element. This invention partially replaces the austenite stabilizing function of Ni through the synergistic effect of high nitrogen and appropriate amount of Mn, controlling the Ni content at 5.0-8.0%, thus significantly reducing alloy cost while ensuring microstructure stability.
[0013] Mo (Mo): 1.6-3.0%. Molybdenum is a key element in improving the pitting and crevice corrosion resistance of stainless steel. Mo can enhance the stability of the passivation film, especially in the presence of Cl. - MoO4 in the environment 2- The form is enriched at the passivation film / solution interface, effectively repelling Cl. - The adsorption of these substances inhibits the initiation and spread of pitting corrosion.
[0014] Cu (copper): 0.8-2.0%. In salt spray environments, copper can form a Cu-enriched layer or adsorbed protective layer on the material surface, effectively inhibiting Cl- buildup. - Erosion of the passivation film. Cu and Mo work synergistically to form a dual corrosion resistance mechanism: Mo resists pitting corrosion, while Cu resists salt spray adsorption.
[0015] Nitrogen (N): 0.20-0.40% (matrix) + gradient nitrogen-rich layer (0.35-0.60% on the surface). Nitrogen is one of the most critical elements in this invention. Nitrogen has multiple beneficial effects: stabilizing austenitic structure, interstitial solid solution strengthening, and enhancing the density and stability of the passivation film. In this invention, the nitrogen content in the matrix is increased to 0.20-0.40%, which is higher than that in conventional high-nitrogen steel, providing a sufficient nitrogen source for the subsequent formation of VN nano-precipitates. Simultaneously, a high-nitrogen gradient layer (0.35-0.60%) is constructed on the surface through atmospheric solution treatment, providing excellent surface corrosion resistance.
[0016] Vanadium (V): 0.02-0.15%. Vanadium is the core element for achieving nanoprecipitation strengthening in this invention. V has a strong affinity for nitrogen (N) and can precipitate as VN and / or V(C,N) under appropriate heat treatment conditions, forming nanoscale precipitates. These nanoscale precipitates are coherent or semi-coherent with the austenitic matrix, producing a strong precipitation strengthening effect and significantly improving the yield strength of the material.
[0017] RE (Rare Earth Elements): 0.01-0.10%. Rare earth elements have the functions of deoxidation, desulfurization, grain refinement, and improvement of inclusion morphology. This invention uses at least one of Ce, La, and Y, preferably a Ce-La-Y ternary composite addition, to reduce the size and improve the morphology of inclusions, and increase the grain size. The rare earth elements are added after the molten steel has been fully deoxidized and desulfurized, using the wire feeding method or the pure iron foil wrapping method. After addition, the mixture is stirred with bottom-blown argon gas for 5-10 minutes to ensure uniform distribution.
[0018] P, S: Strictly control P≤0.030% and S≤0.0020% to ensure the purity and corrosion resistance of the material.
[0019] Preferably, the V content is 0.04-0.12%, and the V / N content satisfies V / N≥0.15, ensuring a stable stoichiometric ratio between vanadium and nitrogen. This allows most of the vanadium in the steel to be fully precipitated as VN or V(C,N) nano-precipitates, rather than dissolved in the matrix. When the ratio of vanadium to nitrogen satisfies this relationship, nitrogen preferentially combines with vanadium to form finely dispersed VN precipitates. These precipitates form coherent or semi-coherent interfaces with the austenitic matrix, producing a strong precipitation strengthening effect. At the same time, the formation of VN precipitates effectively inhibits the combination of nitrogen and chromium to form Cr2N, preventing the consumption of chromium in the matrix and thus protecting corrosion resistance. This significantly improves the yield strength while ensuring the material's resistance to salt spray corrosion.
[0020] Preferably, the depth of the nitrogen diffusion layer is 0.5-3.0 mm, the thickness of the V-containing nitride precipitate phase layer is 5-50 μm, and the thickness of the graphene composite coating is 1-5 μm.
[0021] Preferably, the V-nitride precipitate layer contains VN and / or V(C,N) nanoprecipitates with a volume fraction of 0.5-5.0%.
[0022] Preferably, a laser-guided micropore anchoring layer is provided between the V-containing nitride precipitate phase layer and the graphene composite coating. This layer comprises an array of micropores with a diameter of 10-100 μm, a depth of 5-50 μm, and a spacing of 50-500 μm. The micropore array processed by pulsed laser provides mechanical anchoring points for the graphene composite coating. After the coating material penetrates into the micropores and cures, it forms a mechanical interlock, solving the problem of insufficient interfacial bonding strength in traditional coatings.
[0023] Specifically, the pitting corrosion resistance equivalent PREN of the stainless steel is calculated as: PREN = %Cr + 3.3 × %Mo + 30 × %N - %Mn ≥ 28.0. PREN is a recognized empirical criterion for evaluating the pitting corrosion resistance of stainless steel. Cr, Mo, and N can all significantly improve the stability of the passivation film in a chloride ion environment, while Mn has an adverse effect on pitting corrosion resistance and should be deducted. This invention, through the synergistic ratio of Cr (19.0-22.0%), Mo (1.5-3.0%), and N (0.20-0.40%), controls PREN above 28.0, ensuring that the material has pitting corrosion resistance equivalent to or even superior to that of super austenitic stainless steel. This results in a stable pitting potential of over 300mV, meeting the stringent requirements of high-salt-fog marine environments for chloride ion pitting corrosion resistance.
[0024] On the other hand, the present invention also discloses a method for preparing the above-mentioned salt spray corrosion resistant stainless steel, comprising the following steps: (1) Prepare the raw materials according to the designed chemical composition and refine them. Add V in the middle of the refining process to form molten steel. Add RE at the end of the refining process after the molten steel has been fully deoxidized and desulfurized. At the same time, perform nitrogen enrichment treatment on the molten steel to make the N content in the molten steel reach 0.20-0.40%. (2) The molten steel is cast and cooled to obtain an ingot; (3) Forge or hot roll the ingot into a billet, and cool it after final forging / rolling; (4) Perform solid solution treatment under nitrogen atmosphere, with nitrogen pressure of 0.5-2.0 atm, solid solution temperature of 1050-1150℃, and heat preservation time of 1-3h, so that the nitrogen concentration on the surface layer is increased to 0.35-0.60% to form a nitrogen diffusion layer, and then cool. (5) Perform low-temperature ion nitriding treatment to form a V-containing nitride precipitate phase layer in situ from the V enriched on the surface; (6) A laser micropore anchoring layer is prepared on the surface of the V-nitride precipitated phase layer; (7) A graphene composite coating is applied to the surface of the laser micropore anchoring layer.
[0025] Preferably, the low-temperature ion nitriding treatment in step (5) is carried out at a temperature of 400-500°C in a nitrogen-hydrogen mixed atmosphere for 0.5-4 hours.
[0026] Preferably, the laser micro-hole anchoring layer in step (6) is processed by pulsed laser with a laser power of 10-100W, a pulse frequency of 10-100kHz, and a scanning speed of 100-1000mm / s.
[0027] Preferably, the graphene composite coating in step (7) is an organic resin composite coating doped with graphene or graphene oxide.
[0028] Preferably, the graphene composite coating contains 0.5-5.0% graphene or graphene oxide by mass, has a coating thickness of 1-5 μm, a curing temperature of ≤200℃, and a curing time of 0.5-2 h. The coating method can be spraying or dipping, with the coating material penetrating into the laser micropores and forming a mechanically interlocking structure after curing.
[0029] The beneficial effects of this invention are as follows: This invention constructs a continuously decreasing nitrogen concentration gradient from the surface to the core through atmospheric solution treatment, enhancing the stability of the passivation film with a high-nitrogen surface layer and providing a sufficient nitrogen source for the in-situ formation of VN nano-precipitates during subsequent ion nitriding. Through the synergistic effect of V microalloying and low-temperature ion nitriding, a large number of dispersed VN and / or V(C,N) nano-precipitates are formed on the surface, significantly improving material strength by utilizing the coherent strengthening effect of VN and the austenitic matrix. By constructing a laser micropore array on the surface of the V-nitride precipitate layer, the graphene composite coating penetrates into the micropores to form a mechanically interlocked structure, significantly improving the interfacial bonding strength between the coating and the substrate. Through an ultra-low carbon, high nitrogen, Mo, and Cu composite corrosion-resistant design, it inhibits Cr... 23 C6 precipitation, enhanced passivation film stability, and resistance to Cl- - Multiple mechanisms, including pitting corrosion and the formation of a surface adsorption protective layer, work together to improve corrosion resistance. Detailed Implementation
[0030] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0031] It should be noted that all reagents and raw materials used in this invention are commercially available, and the reagents are of analytical grade.
[0032] The graphene powder is from Changzhou Sixth Element Materials Technology Co., Ltd., model number SE1430. The epoxy resin is from Henan Chiao Trading Co., Ltd., model number NPEL128.
[0033] Example 1 This embodiment provides a salt spray corrosion resistant stainless steel, formulated with the following chemical composition by mass percentage: C 0.035%, Si 0.55%, Mn 4.50%, Cr 20.50%, Ni 6.50%, Mo 2.25%, Cu 1.40%, N 0.30%, V 0.08%, RE (mass ratio Ce:La:Y=1:0.55:0.25) 0.04%, P 0.018%, S 0.0012%, with the balance being Fe and unavoidable impurities. V / N=0.08 / 0.30=0.267. After atmospheric solution treatment, the measured surface nitrogen content Ns is 0.45%. The pitting corrosion resistance equivalent of the stainless steel is: PREN=%Cr+3.3×%Mo+30×%N-%Mn=20.5+3.3×2.25+30×0.30-4.5=32.425.
[0034] Preparation method: (1) Smelting: Vacuum induction melting was used with a vacuum degree of 0.8 Pa. 50 kg of the following materials were weighed according to the specified ratio: industrial pure iron, micro-carbon ferrochrome (FeCr55C0.03), electrolytic nickel (Ni9996), ferromolybdenum (FeMo60), electrolytic manganese (DJMn99.7), electrolytic copper (Cu-CATH-1), metallic silicon (Si1101), metallic vanadium (V-1), rare earth metals (Ce, La, Y), and ferrochrome nitride (FeCrN8). The feeding sequence is as follows: first, add industrial pure iron, micro-carbon ferrochrome, electrolytic nickel, and ferromolybdenum, melt and refine at 1590℃ for 25 minutes, and carry out deoxidation and desulfurization treatment to make the O in the molten steel ≤30ppm and S ≤0.0020%; After the above raw materials have completely melted, add electrolytic manganese, electrolytic copper, and metallic silicon, and stir until homogeneous; Metallic vanadium is added during the middle stage of refining. After addition, the melting temperature is maintained at 1600℃ and electromagnetic stirring is carried out for 6 minutes. Rare earth metals (Ce, La, Y) are added at the end of refining and after the molten steel has been fully deoxidized and desulfurized. The temperature of the molten steel is controlled at 1585℃ during addition. The metals are added by wrapping them in pure iron foil and then stirred with bottom-blowing argon gas for 8 minutes. Simultaneously, ferrochromium nitride is added to the molten steel for nitrogen enrichment treatment, so that the nitrogen content in the molten steel reaches 0.30%; (2) Casting: The molten steel is cast into ingots at a casting temperature of 1500℃. After casting, the ingots are cooled to room temperature using a water-cooled copper mold at a cooling rate of 15℃ / s to obtain the billet. (3) Hot working: The billet is heated to 1180°C at a rate of 10°C / min, held for 2.5h and then forged. The final forging temperature is 985°C. After the final forging, it is immediately water cooled to room temperature at a rate of 50°C / s. (4) Atmosphere solution treatment: The forged material is placed in an atmosphere solution treatment furnace, and nitrogen is introduced. The nitrogen pressure is 1.2 atm, and the temperature is raised to 1090℃ at a rate of 10℃ / min. The temperature is held for 2 hours. During the holding process, nitrogen atoms diffuse from the surface to the inside, and the nitrogen concentration on the surface increases to 0.45%, forming a nitrogen diffusion layer with a depth of about 1.8 mm. After the holding is completed, the material is immediately water-cooled to room temperature at a rate of 60℃ / s. (5) Low-temperature ion nitriding treatment: The material after atmospheric solution treatment is placed in an ion nitriding furnace, evacuated to 8 Pa, and a nitrogen-hydrogen mixed atmosphere (volume ratio, N2:H2=1:2.5) is introduced. The temperature is 440℃, the treatment time is 2h, the voltage is 700V, and the current density is 5mA / cm. 2 Under these conditions, the V enriched on the surface reacts in situ with the infiltrated nitrogen atoms to generate VN and V(C,N) nano-precipitates, forming a V-containing nitride precipitate layer with a thickness of about 25 μm and a volume fraction of about 2.5%. (6) Laser micropore anchoring layer preparation: A micropore array was fabricated on the surface of the V nitride precipitate phase layer using a pulsed laser. The laser power was 50W, the pulse frequency was 50kHz, the scanning speed was 500mm / s, the aperture was 50μm, the depth was 30μm, the spacing between the pores was 200μm, and the micropores were arranged in a square grid. (7) Coating with graphene composite coating: Prepare graphene / epoxy resin composite coating: Disperse graphene powder in epoxy resin at a mass fraction of 2.0%, add curing agent (CK-5106) of 50% of epoxy resin mass, stir evenly, coat by spraying, coating thickness of 2.5μm, coating material penetrates into laser micropores, and finally cure at 150℃ for 1h.
[0035] Example 2 This embodiment provides a salt spray corrosion resistant stainless steel, formulated with the following chemical composition by mass percentage: C 0.020%, Si 0.30%, Mn 3.00%, Cr 20.00%, Ni 5.00%, Mo 1.60%, Cu 0.80%, N 0.20%, V 0.04%, RE (mass ratio Ce:La:Y=1:0.3:0.1) 0.01%, P 0.025%, S 0.0018%, with the balance being Fe and unavoidable impurities. V / N=0.04 / 0.20=0.20. After atmospheric solution treatment, the measured surface nitrogen content Ns is 0.35%. The pitting corrosion resistance equivalent of the stainless steel is: PREN=20.0+3.3×1.6+30×0.20-3=28.28.
[0036] Preparation method: (1) Smelting: Vacuum induction melting was used with a vacuum degree of 0.8 Pa. 50 kg of the following materials were weighed according to the specified ratio: industrial pure iron, micro-carbon ferrochrome (FeCr55C0.03), electrolytic nickel (Ni9996), ferromolybdenum (FeMo60), electrolytic manganese (DJMn99.7), electrolytic copper (Cu-CATH-1), metallic silicon (Si1101), metallic vanadium (V-1), rare earth metals (Ce, La, Y), and ferrochrome nitride (FeCrN8). The feeding sequence is as follows: first, add industrial pure iron, micro-carbon ferrochrome, electrolytic nickel, and ferromolybdenum, melt and refine at 1560℃ for 15 minutes, and carry out deoxidation and desulfurization treatment to make the O in the molten steel ≤30ppm and S ≤0.0020%; After the above raw materials have completely melted, add electrolytic manganese, electrolytic copper, and metallic silicon, and stir until homogeneous; Metallic vanadium is added during the middle stage of refining. After addition, the melting temperature is maintained at 1600℃ and electromagnetic stirring is carried out for 6 minutes. Rare earth metals (Ce, La, Y) are added at the end of refining and after the molten steel has been fully deoxidized and desulfurized. The temperature of the molten steel is controlled at 1585℃ during addition. The metals are added by wrapping them in pure iron foil and then stirred with bottom-blowing argon gas for 8 minutes. Simultaneously, ferrochromium nitride is added to the molten steel for nitrogen enrichment treatment, so that the nitrogen content in the molten steel reaches 0.20%; (2) Casting: The molten steel is cast into ingots at a casting temperature of 1480℃. After casting, the ingots are cooled to room temperature using a water-cooled copper mold at a cooling rate of 12℃ / s to obtain the billet. (3) Hot working: The billet is heated to 1150°C at a rate of 10°C / min, held for 1.5h and then hot rolled. The final rolling temperature is 980°C. After the final rolling, it is immediately water cooled to room temperature at a rate of 50°C / s. (4) Atmosphere solution treatment: The forged material is placed in an atmosphere solution treatment furnace, nitrogen is introduced, the nitrogen pressure is 0.5 atm, the temperature is raised to 1050℃ at a rate of 10℃ / min, and held for 1h. During the holding process, nitrogen atoms diffuse from the surface to the inside, the nitrogen concentration on the surface increases to 0.35%, and a nitrogen diffusion layer with a depth of about 0.5mm is formed. After the holding is completed, the material is immediately water-cooled to room temperature at a rate of 60℃ / s. (5) Low-temperature ion nitriding treatment: The material after atmospheric solution treatment is placed in an ion nitriding furnace, the vacuum is drawn to 8 Pa, a nitrogen-hydrogen mixed atmosphere (volume ratio, N2:H2=1:1) is introduced, the temperature is 400℃, the treatment time is 0.5h, the voltage is 700V, and the current density is 5mA / cm. 2 Under these conditions, the V enriched on the surface reacts in situ with the infiltrated nitrogen atoms to generate VN and V(C,N) nano-precipitates, forming a V-containing nitride precipitate layer with a thickness of about 5 μm and a volume fraction of about 0.5%. (6) Laser micropore anchoring layer preparation: A micropore array was processed on the surface of the V nitride precipitate phase layer using a pulsed laser. The laser power was 10W, the pulse frequency was 10kHz, the scanning speed was 1000mm / s, the processing aperture was 10μm, the hole depth was 50μm, the hole spacing was 500μm, and the micropores were arranged in a square grid. (7) Coating with graphene composite coating: Prepare graphene / epoxy resin composite coating: Disperse graphene powder in epoxy resin at a mass fraction of 0.5%, add curing agent (CK-5106) of 50% of epoxy resin mass, stir evenly, coat by spraying, coating thickness of 1.0 μm, coating material penetrates into laser micropores, and finally cure at 120℃ for 1h.
[0037] Example 3 This embodiment provides a salt spray corrosion resistant stainless steel, formulated with the following chemical composition by mass percentage: C 0.050%, Si 0.80%, Mn 6.00%, Cr 22.00%, Ni 8.00%, Mo 3.00%, Cu 2.00%, N 0.40%, V 0.15%, RE (mass ratio Ce:La:Y=1:0.8:0.4) 0.10%, P 0.015%, S 0.0010%, with the balance being Fe and unavoidable impurities. V / N=0.15 / 0.40=0.375. After atmospheric solution treatment, the measured surface nitrogen content Ns is 0.60%. The pitting corrosion resistance equivalent of the stainless steel is: PREN=22.0+3.3×3.0+30×0.40-6.0=37.9.
[0038] Preparation method: (1) Smelting: Vacuum induction melting was used with a vacuum degree of 0.5 Pa. 50 kg of the following materials were weighed according to the specified ratio: industrial pure iron, micro-carbon ferrochrome (FeCr55C0.03), electrolytic nickel (Ni9996), ferromolybdenum (FeMo60), electrolytic manganese (DJMn99.7), electrolytic copper (Cu-CATH-1), metallic silicon (Si1101), metallic vanadium (V-1), rare earth metals (Ce, La, Y), and ferrochrome nitride (FeCrN8). The feeding sequence is as follows: first, add industrial pure iron, micro-carbon ferrochrome, electrolytic nickel, and ferromolybdenum, melt and refine at 1620℃ for 30 minutes, and carry out deoxidation and desulfurization treatment to make the O in the molten steel ≤30ppm and S ≤0.0020%; After the above raw materials have completely melted, add electrolytic manganese, electrolytic copper, and metallic silicon, and stir until homogeneous; Metallic vanadium is added during the middle stage of refining. After addition, the melting temperature is maintained at 1600℃ and electromagnetic stirring is carried out for 6 minutes. Rare earth metals (Ce, La, Y) are added at the end of refining and after the molten steel has been fully deoxidized and desulfurized. The temperature of the molten steel is controlled at 1585℃ during addition. The metals are added by wrapping them in pure iron foil and then stirred with bottom-blowing argon gas for 8 minutes. Simultaneously, ferrochromium nitride is added to the molten steel for nitrogen enrichment treatment, so that the nitrogen content in the molten steel reaches 0.40%; (2) Casting: The molten steel is cast into ingots at a casting temperature of 1520℃. After casting, the ingots are cooled to room temperature using a water-cooled copper mold at a cooling rate of 18℃ / s to obtain the billet. (3) Hot working: The billet is heated to 1200℃ at a rate of 10℃ / min, held for 3h and then forged. The final forging temperature is 1020℃. After final rolling, it is immediately water cooled to room temperature at a rate of 50℃ / s. (4) Atmosphere solution treatment: The forged material is placed in an atmosphere solution treatment furnace, and nitrogen is introduced. The nitrogen pressure is 2.0 atm, and the temperature is raised to 1150℃ at a rate of 10℃ / min. The temperature is held for 3 hours. During the holding process, nitrogen atoms diffuse from the surface to the inside, and the nitrogen concentration on the surface increases to 0.6%, forming a nitrogen diffusion layer with a depth of about 3.0 mm. After the holding is completed, the material is immediately water-cooled to room temperature at a rate of 60℃ / s. (5) Low-temperature ion nitriding treatment: The material after atmospheric solution treatment is placed in an ion nitriding furnace, the vacuum is drawn to 8 Pa, a nitrogen-hydrogen mixed atmosphere (volume ratio, N2:H2=1:4) is introduced, the temperature is 500℃, the treatment time is 4h, the voltage is 700V, and the current density is 5mA / cm. 2 Under these conditions, the V enriched on the surface reacts in situ with the infiltrated nitrogen atoms to generate VN and V(C,N) nano-precipitates, forming a V-containing nitride precipitate layer with a thickness of about 25 μm and a volume fraction of about 5.0%. (6) Laser micropore anchoring layer preparation: A micropore array was processed on the surface of the V nitride precipitate phase layer using a pulsed laser. The laser power was 100W, the pulse frequency was 100kHz, the scanning speed was 100mm / s, the processing aperture was 100μm, the hole depth was 50μm, the hole spacing was 50μm, and the micropores were arranged in a square grid. (7) Coating with graphene composite coating: Prepare graphene / epoxy resin composite coating: Disperse graphene powder in epoxy resin at a mass fraction of 5.0%, add curing agent (CK-5106) at a mass fraction of 50% of epoxy resin, stir evenly, coat by spraying, coating thickness of 5.0μm, coating material penetrates into laser micropores, and finally cure at 200℃ for 2h.
[0039] Example 4 This embodiment provides a salt spray corrosion resistant stainless steel, formulated with the following chemical composition by mass percentage: C 0.028%, Si 0.45%, Mn 5.20%, Cr 20.80%, Ni 7.20%, Mo 2.60%, Cu 1.60%, N 0.32%, V 0.10%, RE (mass ratio Ce:La:Y=1:0.6:0.2) 0.06%, P 0.020%, S 0.0014%, with the balance being Fe and unavoidable impurities. V / N=0.10 / 0.32=0.313. After atmospheric solution treatment, the measured surface nitrogen content Ns is 0.50%. The pitting corrosion resistance equivalent of the stainless steel is: PREN=20.8+3.3×2.6+30×0.32-5.2=33.78.
[0040] Preparation method: (1) Smelting: Vacuum induction melting was used with a vacuum degree of 0.8 Pa. 50 kg of the following materials were weighed according to the specified ratio: industrial pure iron, micro-carbon ferrochrome (FeCr55C0.03), electrolytic nickel (Ni9996), ferromolybdenum (FeMo60), electrolytic manganese (DJMn99.7), electrolytic copper (Cu-CATH-1), metallic silicon (Si1101), metallic vanadium (V-1), rare earth metals (Ce, La, Y), and ferrochrome nitride (FeCrN8). The feeding sequence is as follows: first, add industrial pure iron, micro-carbon ferrochrome, electrolytic nickel, and ferromolybdenum, melt and refine at 1580℃ for 22 minutes, and carry out deoxidation and desulfurization treatment to make the O in the molten steel ≤30ppm and S ≤0.0020%; After the above raw materials have completely melted, add electrolytic manganese, electrolytic copper, and metallic silicon, and stir until homogeneous; Metallic vanadium is added during the middle stage of refining. After addition, the melting temperature is maintained at 1600℃ and electromagnetic stirring is carried out for 6 minutes. Rare earth metals (Ce, La, Y) are added at the end of refining and after the molten steel has been fully deoxidized and desulfurized. The temperature of the molten steel is controlled at 1585℃ during addition. The metals are added by wrapping them in pure iron foil and then stirred with bottom-blowing argon gas for 8 minutes. Simultaneously, ferrochromium nitride is added to the molten steel for nitrogen enrichment treatment, so that the nitrogen content in the molten steel reaches 0.32%; (2) Casting: The molten steel is cast into ingots at a casting temperature of 1495℃. After casting, the ingots are cooled to room temperature using a water-cooled copper mold at a cooling rate of 14℃ / s to obtain the billet. (3) Hot working: The billet is heated to 1170°C at a rate of 10°C / min, held for 2.5h and then hot rolled. The final rolling temperature is 965°C. After the final forging, it is immediately water cooled to room temperature at a rate of 50°C / s. (4) Atmosphere solution treatment: The forged material is placed in an atmosphere solution treatment furnace, and nitrogen is introduced. The nitrogen pressure is 1.5 atm, and the temperature is raised to 1080℃ at a rate of 10℃ / min. The temperature is held for 1.8h. During the holding process, nitrogen atoms diffuse from the surface to the inside, and the nitrogen concentration on the surface increases to 0.5%, forming a nitrogen diffusion layer with a depth of about 2.2mm. After the holding is completed, the material is immediately water-cooled to room temperature at a rate of 60℃ / s. (5) Low-temperature ion nitriding treatment: The material after atmospheric solution treatment is placed in an ion nitriding furnace, evacuated to 8 Pa, and a nitrogen-hydrogen mixed atmosphere (volume ratio, N2:H2=1:3) is introduced. The temperature is 450℃, the treatment time is 2.5h, the voltage is 700V, and the current density is 5mA / cm. 2 Under these conditions, the V enriched on the surface reacts in situ with the infiltrated nitrogen atoms to generate VN and V(C,N) nano-precipitates, forming a V-containing nitride precipitate layer with a thickness of about 25 μm and a volume fraction of about 2.5%. (6) Laser micropore anchoring layer preparation: A micropore array was fabricated on the surface of the V nitride precipitate layer using a pulsed laser. The laser power was 60W, the pulse frequency was 60kHz, the scanning speed was 300mm / s, the aperture was 60μm, the depth was 35μm, the spacing between the pores was 150μm, and the micropores were arranged in a square grid. (7) Coating with graphene composite coating: Prepare graphene / epoxy resin composite coating: Disperse graphene powder in epoxy resin at a mass fraction of 3.0%, add curing agent (CK-5106) of 50% of epoxy resin mass, stir evenly, coat by spraying, coating thickness of 3.0μm, coating material penetrates into laser micropores, and finally cure at 160℃ for 1h.
[0041] Comparative Example 1 Compared with Example 1, the difference is that the atmospheric solution treatment in step (4) is cancelled and replaced with conventional Ar atmosphere uniform solution treatment (1090℃, 2h, Ar atmosphere protection) so that N is uniformly distributed in the matrix (surface N content ≈ core N content ≈ 0.30%), and no gradient nitrogen distribution is formed.
[0042] Comparative Example 2 Compared with Example 1, the difference is that the atmospheric solution treatment in step (4) is cancelled and replaced with conventional Ar atmosphere uniform solution treatment (1090℃, 2h, Ar atmosphere protection) so that N is uniformly distributed in the matrix (surface N content ≈ core N content ≈ 0.30%), without forming a gradient nitrogen distribution, and no metallic vanadium is added (V=0%).
[0043] Comparative Example 3 The difference compared to Example 1 is that no metallic vanadium is added.
[0044] Comparative Example 4 The difference compared to Example 1 is that the V content is 0.010% and V / N = 0.033 < 0.15.
[0045] Comparative Example 5 Compared with Example 1, the difference is that the V content is adjusted to 0.03%, the N content is adjusted to 0.30%, and V / N = 0.10 < 0.15.
[0046] Comparative Example 6 The difference compared to Example 1 is that no rare earth metals are added during smelting.
[0047] Comparative Example 7 Compared with Example 1, the difference is that the low-temperature ion nitriding treatment in step (5) is cancelled, and the laser micro-hole processing is performed directly after the atmospheric solution treatment.
[0048] Comparative Example 8 Compared with Example 1, the difference is that step (6) of preparing the laser micropore anchoring layer is cancelled, and the graphene composite coating is directly coated on the surface of the V-nitride precipitated phase layer. The coating conditions are the same as those in Example 1.
[0049] Comparative Example 9 The difference from Example 1 is that step (7) of applying the graphene composite coating is omitted.
[0050] The stainless steel samples obtained in Examples 1-4 and Comparative Examples 1-9 were subjected to relevant performance tests. The test indicators and methods are as follows: Neutral salt spray test (NSS): The test was conducted according to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", using a 5% NaCl solution, pH 6.8, and a test temperature of 35±2℃. Continuous spraying was performed, and the time when the first red rust appeared on the sample surface was recorded. Three parallel samples were taken for each sample, and the average value was taken.
[0051] Pitting potential: Tested according to GB / T 17899-2023 "Corrosion of metals and alloys - Potentiodynamic measurement method for pitting potential of stainless steel in sodium chloride solution". The test was conducted in 3.5% NaCl solution at 25±1℃ using the potentiodynamic polarization method at a scan rate of 0.1667 mV / s and a current density of 100 μA / cm². 2 The pitting potential (vs. SCE) was used as the pitting potential to evaluate the material's resistance to chloride ion pitting corrosion. Three parallel samples were taken for each sample, and the results were averaged.
[0052] Intergranular corrosion test: The test was conducted according to Method E (sulfuric acid-copper sulfate method) in GB / T 4334-2020 "Corrosion of metals and alloys, austenitic and ferritic (duplex) stainless steel". After the sample was sensitized at 650℃ for 2 hours, it was boiled in sulfuric acid-copper sulfate solution for 16 hours. After bending 180°, the surface was observed for cracks to evaluate the material's ability to resist intergranular corrosion in the sensitized state.
[0053] Yield strength: A room temperature tensile test was conducted according to GB / T 228.1-2021 "Metallic materials, tensile testing—Part 1: Test at room temperature," with a yield strength of 0.00025 s⁻¹. -1 The strain rate determination specifies a plastic elongation strength Rp ≤ 0.2 to evaluate the material's resistance to plastic deformation. Three parallel samples are taken for each sample, and the results are averaged.
[0054] Cross-cut test of coating: The test shall be conducted in accordance with GB / T 9286-2021 "Cross-cut test of paints and varnishes". A grid array shall be drawn on the surface of the coating with a cross-cut knife. After peeling off with standard tape, the coating shall be rated from 0 to 5 according to the percentage of peeled area to evaluate the bonding strength between the coating and the substrate.
[0055] Pull-off adhesion test: The test was conducted according to GB / T 5210-2006 "Paints and Varnishes - Pull-off Adhesion Test". A tensile force perpendicular to the coating surface was applied at a specified loading rate using the bonded tensile method with paired specimens. The maximum stress (MPa) at which the coating peels off from the substrate was measured to quantitatively evaluate the interfacial bonding strength between the coating and the substrate. Three parallel samples were taken for each sample, and the average value was used.
[0056] The performance test results are shown in Table 1.
[0057] Table 1 Performance Test Results
[0058] As shown in the table above, the embodiments of the present invention outperform the comparative examples in key performance aspects. The specific reasons are as follows: Comparative Example 1 eliminated the atmospheric solution treatment, thus failing to form a gradient nitrogen distribution, but retained V. Since the surface N content was only 0.30% of the uniform core content, the passivation film enhancement effect of a high-nitrogen (0.45%) surface layer could not be formed; simultaneously, the lack of a high-concentration N enrichment environment for surface V resulted in insufficient thermodynamic driving force for VN precipitation, and precipitation strengthening was not fully realized, leading to a 28.2% decrease in NSS salt spray and a 12.7% decrease in yield strength compared to Example 1. Comparative Example 3 retained the gradient nitrogen distribution but did not add V. Due to the absence of V in the matrix, even with the gradient nitrogen distribution providing a high-nitrogen environment on the surface, VN nanoprecipitates could not be formed, resulting in a complete lack of precipitation strengthening effect, leading to a 29.1% decrease in yield strength compared to Example 1, the largest decrease among all comparative examples. Comparative Example 2 simultaneously eliminated the gradient nitrogen distribution and did not add V. Since there was neither a high-nitrogen passivation film nor VN precipitation reinforcement on the surface, both reinforcement mechanisms were absent, resulting in a 41.5% decrease in NSS salt spray performance and a 39.0% decrease in yield strength compared to Example 1, both being the worst among all comparison examples. These results demonstrate that the gradient nitrogen distribution provides a high-nitrogen environment on the surface for VN precipitation, and V utilizes this environment to form the VN precipitated phase; the two constitute a coupled reinforcement chain of "nitrogen supply-precipitation." The performance significantly decreased when either element was absent alone, and the performance deterioration when both were absent simultaneously far exceeded the simple superposition of single absences, proving that both are indispensable and interdependent.
[0059] Comparative Example 3, without the addition of V, had a yield strength of only 356 MPa. Comparative Example 4 reduced the V content to 0.010% (below the lower limit of 0.02% in this invention). Although a very small amount of V was present, the absolute amount of V was insufficient to form a sufficient amount of VN precipitate, resulting in a yield strength increase of only 385 MPa, still far lower than the 502 MPa of Example 1. In Comparative Example 5, the V content was 0.03% (within the range defined by this invention), and the N content was 0.30%, but V / N = 0.10 < 0.15. Because the ratio of vanadium to nitrogen did not reach the stoichiometric threshold for VN precipitation, most of the V remained dissolved in the matrix and failed to precipitate completely, limiting the precipitation strengthening effect, resulting in a yield strength of only 398 MPa. The above results indicate that there is a critical threshold for V content; when it is below 0.02%, even with sufficient N source, an effective amount of VN precipitate cannot be formed. At the same time, the quantitative constraint relationship of V / N ≥ 0.15 is an independent necessary condition to ensure sufficient V precipitation—even if V and N each meet the content range, if their ratio is imbalanced, precipitation enhancement cannot be maximized.
[0060] In Comparative Example 6, without the addition of rare earth elements, the inclusions, which remain in the form of elongated MnS due to the lack of modification treatment by Ce, La, and Y, became the preferred origin sites for pitting corrosion. Simultaneously, the grain refinement effect was weakened, the microstructure uniformity decreased, and the passivation film density reduced, resulting in a 7.5% decrease in NSS salt spray and an 11.2% decrease in pitting potential compared to Example 1. This indicates that the addition of rare earth elements improves corrosion resistance through a dual mechanism of inclusion modification and grain refinement, ensuring stable corrosion resistance, especially in long-term salt spray tests.
[0061] Comparative Example 7 omitted the low-temperature ion nitriding treatment. Although a gradient nitrogen distribution was formed and the contents of V and N were sufficient, due to the lack of energy and kinetic conditions provided by the ion nitriding process, V and N could not obtain sufficient migration and reaction driving forces to generate VN precipitates in situ. Most of V remained in the matrix in a solid solution state, resulting in a yield strength of only 342 MPa, a decrease of 31.9% compared to Example 1. This demonstrates that low-temperature ion nitriding is a necessary process condition for achieving in-situ precipitation of VN—composition design provides the material basis, and ion nitriding provides the reaction driving force; both are indispensable. Without corresponding process guarantees, precipitation strengthening cannot be achieved with only composition design.
[0062] Comparative Example 8: The laser micropore anchoring layer was removed. Because the graphene coating and the substrate only have a simple planar interface bond, lacking the mechanical interlocking effect provided by the micropores, the bonding strength between the coating and the substrate is severely insufficient. The pull-off adhesion is only 8.5 MPa (a 55.2% decrease compared to Example 1), and the cross-cut adhesion test rating deteriorates from level 0 to level 3. During salt spray corrosion, the coating peels laterally along the interface, prematurely failing and exposing the substrate, reducing the NSS salt spray level to 720 h. Comparative Example 9: The graphene composite coating was removed. Although the laser micropore anchoring layer structure is complete, it lacks the physical barrier function of the outermost graphene layer. - Direct attack on the V-containing nitride precipitate phase layer accelerates the corrosion process, resulting in an NSS salt spray duration of only 588 hours (a 31.0% decrease compared to Example 1), failing to meet the target requirement of ≥720 hours. These results indicate a synergistic protective effect between the laser-guided microporous anchoring layer and the graphene coating—the anchoring layer ensures long-term stable adhesion of the coating, while the coating provides a physical barrier to prevent Cl- buildup. - Both the anchoring layer and the coating are indispensable. When the anchoring layer is missing, the coating has a physical barrier function, but it will peel off prematurely due to insufficient adhesion (Comparative Example 8); when the coating is missing, the anchoring layer has an intact structure but no physical barrier function (Comparative Example 9). The absence of either one will cause the salt spray resistance to drop to 720h or below. Only when both are present can the ultra-long salt spray life of 852h be achieved.
[0063] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, and these simple modifications all fall within the protection scope of the present invention. Furthermore, it should be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe the various possible combinations.
[0064] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A salt spray corrosion resistant stainless steel, characterized in that, The stainless steel includes a stainless steel substrate and a composite protective layer laminated on the surface of the stainless steel substrate. The stainless steel matrix comprises, by mass percentage: C 0.02-0.05%, Si 0.3-0.8%, Mn 3.0-6.0%, Cr 20.0-22.0%, Ni 5.0-8.0%, Mo 1.6-3.0%, Cu 0.8-2.0%, N 0.20-0.40%, V 0.02-0.15%, RE 0.01-0.10%, P≤0.030%, S≤0.0020%, with the balance being Fe and unavoidable impurities; The RE is at least one of the rare earth elements Ce, La and Y; The nitrogen (N) content in the stainless steel matrix exhibits a gradient distribution along the thickness direction, with the surface layer containing 0.35-0.60% Ns and the core containing 0.15-0.25% Nc, and the Ns-Nc ratio ≥ 0.10%. The composite protective layer consists of, from the inside out: a nitrogen diffusion layer, a V-containing nitride precipitate layer, and a graphene composite coating. The V-containing nitride precipitate layer is formed in situ on the surface of the stainless steel substrate.
2. The salt spray corrosion resistant stainless steel according to claim 1, characterized in that, The V content is 0.04-0.12%, and the V and N contents satisfy V / N≥0.
15.
3. The salt spray corrosion resistant stainless steel according to claim 1, characterized in that, The nitrogen diffusion layer has a depth of 0.5-3.0 mm, the V-containing nitride precipitate layer has a thickness of 5-50 μm, and the graphene composite coating has a thickness of 1-5 μm.
4. The salt spray corrosion resistant stainless steel according to claim 1, characterized in that, The V-nitride precipitate layer contains VN and / or V(C,N) nanoprecipitates with a volume fraction of 0.5-5.0%.
5. The salt spray corrosion resistant stainless steel according to claim 1, characterized in that, A laser micropore anchoring layer is provided between the V-containing nitride precipitated phase layer and the graphene composite coating. The laser micropore anchoring layer includes an array of micropores with a pore size of 10-100 μm, a depth of 5-50 μm, and a pore spacing of 50-500 μm.
6. A method for preparing the salt spray corrosion resistant stainless steel according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Prepare the raw materials according to the designed chemical composition and refine them. Add V in the middle of the refining process to form molten steel. Add RE at the end of the refining process after the molten steel has been fully deoxidized and desulfurized. At the same time, perform nitrogen enrichment treatment on the molten steel to make the N content in the molten steel reach 0.20-0.40%. (2) The molten steel is cast and cooled to obtain an ingot; (3) Forge or hot roll the ingot into a billet, and cool it after final forging / rolling; (4) Perform solid solution treatment under nitrogen atmosphere, with nitrogen pressure of 0.5-2.0 atm, solid solution temperature of 1050-1150℃, and heat preservation time of 1-3h, so that the nitrogen concentration on the surface layer is increased to 0.35-0.60% to form a nitrogen diffusion layer, and then cool. (5) Perform low-temperature ion nitriding treatment to form a V-containing nitride precipitate phase layer in situ from the V enriched on the surface; (6) A laser micropore anchoring layer is prepared on the surface of the V-nitride precipitated phase layer; (7) A graphene composite coating is applied to the surface of the laser micro-hole anchoring layer.
7. The method for preparing salt spray corrosion resistant stainless steel according to claim 6, characterized in that, The low-temperature ion nitriding treatment described in step (5) is carried out at a temperature of 400-500℃ in a nitrogen-hydrogen mixed atmosphere for 0.5-4h.
8. The method for preparing salt spray corrosion resistant stainless steel according to claim 6, characterized in that, The laser micro-hole anchoring layer described in step (6) is processed by pulsed laser with a laser power of 10-100W, a pulse frequency of 10-100kHz, and a scanning speed of 100-1000mm / s.
9. The method for preparing salt spray corrosion resistant stainless steel according to claim 6, characterized in that, The graphene composite coating mentioned in step (7) is an organic resin composite coating doped with graphene or graphene oxide.
10. The method for preparing salt spray corrosion resistant stainless steel according to claim 9, characterized in that, The graphene composite coating contains 0.5-5.0% graphene or graphene oxide by mass, has a coating thickness of 1-5 μm, a curing temperature of ≤200℃, and a curing time of 0.5-2 h.
Citation Information
Patent Citations
Stainless steel surface composite infiltrated layer and preparation method and application thereof
CN117684120A
Gradient nitrogen-containing austenitic stainless steel and preparation method and application thereof
CN118996323A